2020
DOI: 10.1186/s12891-020-03220-6
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a multicenter prospective cohort study evaluating sport activity and development of femoroacetabular impingement in the adolescent hip

Abstract: Background: Femoroacetabular impingement (FAI) is an important cause of hip pain in young and active individuals and occurs as a result of size and shape mismatch between the femoral head and acetabulum. Open physes in children can make hips more susceptible to injury, and high impact forces have been suggested to affect the developing femur. The diagnosis of FAI has recently risen, especially within adolescent populations, and there is an increasing trend towards yearround participation in sports with early s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(58 reference statements)
0
4
0
1
Order By: Relevance
“…Por fi m, foram selecionados 17 estudos para a revisão sistemática, que foram lidos por completo para a extração de resultados. Optou-se por retirar da revisão o estudo proposto por Raj et al (2017) 11 :"Chronic kidney disease and sports participation by children and adolescents", por se tratar de uma revisão, além do estudo sugerido por Öhlin et al (2020) 12 : "Protocol for a multicenter prospective cohort study evaluating sport activity and development of femoroacetabular impingement in the adolescent hip", por ser um estudo prévio. Finalizou-se com 15 estudos selecionados.…”
Section: Resultsunclassified
“…Por fi m, foram selecionados 17 estudos para a revisão sistemática, que foram lidos por completo para a extração de resultados. Optou-se por retirar da revisão o estudo proposto por Raj et al (2017) 11 :"Chronic kidney disease and sports participation by children and adolescents", por se tratar de uma revisão, além do estudo sugerido por Öhlin et al (2020) 12 : "Protocol for a multicenter prospective cohort study evaluating sport activity and development of femoroacetabular impingement in the adolescent hip", por ser um estudo prévio. Finalizou-se com 15 estudos selecionados.…”
Section: Resultsunclassified
“…To promote complete data collection and improve participant retention, we added interim follow-up visits every 3 months and introduced an activity log and wrist-worn tracker to improve the collection of physical activity data over the 2-year period. The definitive study protocol has been published [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because this was a pilot to help determine feasibility and generate hypotheses, we were unable to make any definitive conclusions at this time due to the small sample size. We did not meet all of our pre-defined feasibility criteria but were able to adjust the protocol to help ensure the success of the definitive prospective cohort study [ 29 ]. In addition, we expect a higher follow-up rate as the definitive study continues post-COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies published to date on this topic have been cross-sectional survey studies, with only a few examples of high-quality prospective studies 21,22,59 . We are aware of 1 currently ongoing multicenter prospective trial that aims to compare children from 12 to 14 years old who are sport specialists and nonspecialists with respect to the incidence of femoroacetabular impingement (NCT04243447) 60 . A few studies with Level-II and III evidence (Table I) have suggested a possible link between early sport specialization and injury, but this is limited to just 2 prospective studies 21,22 .…”
Section: Practical Solutions To Early Sport Specializationmentioning
confidence: 99%